Generalised anxiety disorder and its determinants amongst patients with diabetes in primary healthcare clinics: a cross-sectional study in Kuwait City, 2024 - Sana Mubarak Alali; Doaa Khalifa Hussein Abdalla; Aisha Alsaqabi; Hessa Al-Kandari; Ozayr Mahomed (BMC Public Health)
Abstract Background Anxiety disorders are the second most common mental health disorders in terms of disability-adjusted life years and years of life lost across all age groups. A bidirectional relationship between anxiety disorders and diabetes mellitus has been documented. This study aimed to determine the prevalence of anxiety and its associated factors among patients with diabetes receiving care at public primary care clinics in Kuwait during the first quarter of 2024. Methodology A cross-sectional study was conducted in the first quarter of 2024 at three primary healthcare centres within the Capital Governate in Kuwait City. Adults with diabetes mellitus for longer than six months duration were requested to participate by the health promoters and the Generalised Anxiety Disorder questionnaire was shared via a mobile link/QR scan. Data were collected through self-or interviewer-administered surveys, cleaned and coded in Microsoft Excel, and analysed using STATA version 18. Descriptive analysis was initially conducted followed by bivariate and multivariate analysis with a p < 0.05 and a 95% confidence interval used to determine the association between demographic and clinical factors and GAD. Results A total of 554 patients participated, yielding an 80% response rate. Anxiety symptoms were observed in 48% of respondents, though only 4% (n = 25) had a GAD score > 10. Among participants with moderate-to-severe anxiety (n = 21), 52% were aged 50–59 years, 90% were non-native Kuwaiti citizens, and 62% had an HbA1C measurement > 7 mmol/L. Multivariate analysis indicated that non-native Kuwait citizens were significantly more likely to have moderate-to-severe anxiety (AOR: 6.99, 95% CI: 1.42–34.43) compared to Kuwaiti nationals. Conversely, participants attending clinic visits every two months were less likely (AOR: 0.30, 95% CI: 0.00–0.50) to report moderate-to-severe anxiety symptoms than those attending monthly. Conclusion While nearly half of patients with diabetes displayed anxiety symptoms, only a small proportion (4%) experienced moderate-to-severe anxiety. Non-native Kuwaiti residents were significantly more likely to have GAD scores > 10. Integrating anxiety screening into diabetes care may improve outcomes for this high-risk group.